Effect of Biodiesel B30 on Deposit Forming and Wear Metal of Diesel Engine Components - Zeka Angger Hartono; Beny Cahyono (Institut Teknologi Sepuluh Nopember, 2020)
Alternative fuels for diesel engines have attracted the world's attention as an impact of the world energy crisis. For this reason, alternative fuel is needed to reduce the need for fossil fuels. Biodiesel fuel with the raw material of palm oil is the once alternative fuel to replace diesel fuel. This is because Indonesia is the largest producer of crude palm oil (CPO) in the world. But, the use of vegetable oil biodiesel can affect losses to engine lifetime. It can increasing metal wear rates in diesel engines. The experiment carried out by running diesel engines for 200 hours with Engine Manufacturer’s Association (EMA) standard. B30 palm oil biodiesel affected the wear metal contact in diesel engines. Aluminum content in used lubricating oil fueled by B30 palm oil biodiesel is 19.8% greater, iron content 0.75% greater, and chromium content greater than metal content in used lubricating oil fueled by diesel fuel. In addition, the use of B30 palm oil biodiesel causes a larger piston ring gap and worse condition on journal bearing. But, deposit forming in the diesel engine components fueled by B30 palm oil biodiesel is 4.27% lower than diesel fuel. It can be concluded that the use of B30 palm oil biodiesel causes greater metal wear than the use of diesel fuel.